Effect of Oxycodone-Based Multimodal Analgesia on Visceral Pain After Major Laparoscopic Gastrointestinal Surgery: A Randomised, Double-Blind, Controlled Trial - Yang GW; Cheng H; Song XY; Yang YF; Liu H; Ji FH; Peng K (Dove Medical Press, 2024)
Guo-Wang Yang,1,2 Hao Cheng,1,2 Xiao-Yang Song,3 Yu-Fan Yang,1,2 Hong Liu,4 Fu-Hai Ji,1,2 Ke Peng1,2 1Department of Anaesthesiology, the First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People's Republic of China; 2Institute of Anaesthesiology, Soochow University, Suzhou, Jiangsu, People's Republic of China; 3Department of Anaesthesiology, the Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou Municipal Hospital, Suzhou, Jiangsu, People's Republic of China; 4Department of Anaesthesiology and Pain Medicine, University of California Davis Health, Sacramento, CA, USACorrespondence: Ke Peng, Department of Anaesthesiology, the First Affiliated Hospital of Soochow University, 188 Shizi St, Suzhou, Jiangsu, 215006, People's Republic of China, Tel +86-15962155989, Email pengke0422@163.comPurpose: Oxycodone is a potent μ- and κ-opioid receptor agonist that can relieve both somatic and visceral pain. We assessed oxycodone- vs sufentanil-based multimodal analgesia on postoperative pain following major laparoscopic gastrointestinal surgery.Methods: In this randomised double-blind controlled trial, 40 adult patients were randomised (1:1, stratified by type of surgery) to receive oxycodone- or sufentanil-based multimodal analgesia, comprising bilateral transverse abdominis plane blocks, intraoperative dexmedetomidine infusion, flurbiprofen axetil, and oxycodone- or sufentanil-based patient-controlled analgesia. The co-primary outcomes were time-weighted average (TWA) of visceral pain (defined as intra-abdominal deep and dull pain) at rest and on coughing during 0- 24 h postoperatively, assessed using the numerical rating scale (0- 10) with a minimal clinically important difference of 1.Results: All patients completed the study (median age, 64 years; 65% male) and had adequate postoperative pain control. The mean (SD) 24-h TWA of visceral pain at rest was 1.40 (0.77) in the oxycodone group vs 2.00 (0.98) in the sufentanil group (mean difference=− 0.60, 95% CI, − 1.16 to − 0.03; P=0.039). Patients in the oxycodone group had a significantly lower 24-h TWA of visceral pain on coughing (2.00 [0.83] vs 2.98 [1.26]; mean difference=− 0.98, 95% CI, − 1.66 to − 0.30; P=0.006). In the subgroup analyses, the treatment effect of oxycodone vs sufentanil on the co-primary outcomes did not differ in terms of age (18- 65 years or > 65 years), sex (female or male), or type of surgery (colorectal or gastric). Secondary outcomes (24-h TWA of incisional and shoulder pain, postoperative analgesic usage, rescue analgesia, adverse events, and patient satisfaction) were comparable between groups.Conclusion: For patients undergoing major laparoscopic gastrointestinal surgery, oxycodone-based multimodal analgesia reduced postoperative visceral pain in a statistically significant but not clinically important manner.Trial Registration: Chinese Clinical Trial Registry (ChiCTR2100052085).Keywords: laparoscopic gastrointestinal surgery, oxycodone, patient-controlled analgesia, visceral pain